Poly(lactide-co-glycolide)-based Micro and Nanoparticles for the Controlled Drug Delivery of Vitamins - Stevanovic, Magdalena; Uskokovic, Dragan (Current Nanoscience, 2009)
Controlled drug delivery systems and polymeric carriers have undergone significant development in recent years. Polymers like polylactides (PLA), polyglycolides (PGA), poly(lactide-co-glycolides) (PLGA), are approved by the World Health Organization (WHO) and Food and Drug Administration (FDA) as materials that can be used in medicine and pharmacy. Owing to their biodegradable nature, polymer materials, such as copolymer poly(DL-lactide-co-glycolide), are widely used in various medical applications; controlled release of delivering drugs, carriers in the tissue engineering, fixation of bone fractures, chirurgical strings, etc. Polymeric particles are used for the controlled delivery of several types of medicaments, including anticancer agents, antihypertensive agents, immunomodulatory drugs, hormones, vitamins and macromolecules, such as nucleic acid, proteins, peptides, antibodies, etc. Preparation of poly(lactideco- glycolide) submicron spheres poses serious challenges. The present review attempts to address some important issues related to micro/ nanoparticle-based delivery systems comprising poly(lactide-co-glycolide), with a special reference to PLGA for the controlled delivery of vitamins. A range of topics is discussed, including formulation aspects of micro- and nanoparticles, the effects of particle size and size distribution, most commonly used incorporation techniques, surface modification with stabilizers, surface functionalization, and factors affecting degradation and drug release rate.
Keywords: drug release